Nutritional quality assessment of Pinasoy: a pineapple and soybean blend drink - Ebabhamiegbebho, P.A.; Evivie, S.E.; Izekor, C. (ADAN JOURNAL OF AGRICULTURE, 2020)
Soybean is a nutrient-dense food which may be used as alternative to animal protein. However, its beany flavour has lowered acceptability levels in soymilk production. In this study, soybeans and pineapple fruit were processed into soymilk and fruit juice, respectively. A total of five soybeans/pineapple blends and a control were produced for proximate analysis and mineral evaluation. The 100% pineapple was observed to contain highest amount of Carbohydrate (11.35%), Fibre (0.12%), Ether extract (0.10%), Crude protein (0.59%), Ash (0.44%), Sodium (10.93mg/l), Calcium (9.25mg/l), Magnesium (28.90mg/l), Potassium (77.53mg/l), and Phosphorus (9.51mg/l). The soymilk was observed to contain Sodium (5.13mg/l), Calcium (5.41mg/l), Magnesium (2.63mg/l), Potassium (33.57mg/l), and Phosphorus (3.09mg/l). The pinasoy blends contained the following range of nutrients: Protein (0.59-3.05%), Carbohydrate (2.76-11.35%), Fibre (0.12-1.76%), Ether extract (0.10-3.52%), Ash (0.44-0.78%), Sodium (4.4-16.77mg/l), Calcium (0.28-10.57mg/l), Magnesium (0.44-28.90mg/l), Potassium (32.10-77.53mg/l), and Phosphorus (0.56-9.51mg/l). The product had high moisture content which ranged from 87.36-89.59%. There were appreciable increase of Carbohydrate and Sodium in all the replaced samples with the highest being observed in sample 90:10% Pineapple/Soybean (P.S) (Carbohydrate 7.00% and Sodium 16.77mg/l). Carbohydrate and Sodium were observed to increase as the level of substitution with fruit juice increased, thus, the beverage could be of high nutritional value and can provide enhanced energy as well as serves as a probable balanced meal for consumers.